Environmental considerations in statutory planning: evolving policies in development plans - Foziah Johar (Environmental Management Society, Malaysia, 2001)
Land use planning is widely regarded as having a significant role to play in achieving or moving towards sustainable development. Through planning functions, environmental impacts can be mitigated, resources conserved and policy tool available to the planning system is that of regulation which works primarily through a mixture of guidance and control. This article examines the role, which the system can play in achieving sustainability particularly relating to the environmental aspects are considerations include the development plan policies; the statutory duty in making planning decision and environmental aspects as a ‘material consideration’. The article further explores the way environmental considerations are being developed in the planning system in the context of this claims, focusing in particular on environmental policies in the development plans. Four main phases of environmental discourse are identified: enhancing amenity concern (pre 1970s); managing growth (1970s to early 1980s); environmental care and management (late 1980s to early 1990s); and integrating sustainable development (1990s onwards). The article concludes with suggestions on ways in which the treatment of the environment in the planning system could evolve